Early generation in vitro assay to identify potato populations and clones tolerant to heat - Khan, A.; Munive, S.; Bonierbale, Merideth W. (Springer, 2015)
An efficient in vitro system for early generation selection of heat-tolerant potato breeding materials was tested and validated in field conditions. At the family level, family groups expected to be heat tolerant due to their genetic background were identified as heat tolerant. In the in vitro assay, LTVR × LTVR, an advanced heat-tolerant breeding population developed at CIP, had 100 % of plants with tubers at 18 °C, 73 % at 25 °C and 2 % at 32 °C in the dark. The results from true seed family level in vitro screening at 25 °C and tuber family evaluation under field conditions in Tacna, an arid sub-tropical environment in Southern Peru, were positively correlated (r = 0.57). There was low to moderate correlation between percentage of plants with tubers under 27 °C in vitro temperature treatment and harvest index in the in vivo conditions in Majes–Arequipa, San Ramon, and La Molina that followed increasing temperature ranges between the sites. This indicates that the methodology can predict putative heat tolerant clones with a low level of confidence. Low correlation is possibly due to differential responses of the clones to characteristics of the growing environment, such as soil versus media, which were not represented in the in vitro assay, as well as the fact that in the field, day–night temperatures vary during tuberization and tuber filling, and throughout the season, while in vitro temperature and the dark period were kept constant, and conditions were controlled specifically to assess tuberization (tuber induction) at high night temperatures. The ability of the in vitro seedling screening assay to identify families tolerant to high temperatures in an inexpensive and less time consuming way without need of transplanting experimental material to the field will facilitate evaluation of significant samples of genetic resources and improved populations in breeding programs attempting to improve potato for adaptation to new environments and climate change.